Antibiotic use and colorectal neoplasia: a systematic review and meta-analysis - Mengmeng Du; Chino Aneke-Nash; Garrett Yoon; Peter Liang (BMJ Open Gastroenterology)
Background and aims Colorectal cancer (CRC) is the third most common cancer for women and men and the second leading cause of cancer death in the USA. There is emerging evidence that the gut microbiome plays a role in CRC development, and antibiotics are one of the most common exposures that can alter the gut microbiome. We performed a systematic review and meta-analysis to characterise the association between antibiotic use and colorectal neoplasia.Methods We searched PubMed, EMBASE, and Web of Science for articles that examined the association between antibiotic exposure and colorectal neoplasia (cancer or adenoma) through 15 December 2019. A total of 6031 citations were identified and 6 papers were included in the final analysis. We assessed the association between the level of antibiotic use (defined as number of courses or duration of therapy) and colorectal neoplasia using a random effects model.Results Six studies provided 16 estimates of the association between level of antibiotic use and colorectal neoplasia. Individuals with the highest levels of antibiotic exposure had a 10% higher risk of colorectal neoplasia than those with the lowest exposure (effect size: 1.10, 95% CI 1.01 to 1.18). We found evidence of high heterogeneity (I2=79%, p=0.0001) but not of publication bias.Conclusions Higher levels of antibiotic exposure is associated with an increased risk of colorectal neoplasia. Given the widespread use of antibiotics in childhood and early adulthood, additional research to further characterise this relationship is needed.